EVALUATION OF NEONATAL MORBIDITY IN PRETERM BIRTH INFANTS - ZAHID , M; TOUHEED , U; AKHTAR , N (Biological and Clinical Sciences Research Journal, 2023)
This study was designed to evaluate neonatal morbidities in late preterm births (38 weeks). A retrospective study was carried out in the hospital's Paediatrics & Gynecology and Obstetrics department from May 2022- May 2023. A total of 100 late preterm infants that were born alive and normal-term infants were selected for the final analysis. Patients were categorized into two groups; Group A consisted of late preterm infants, and Group B included normal-term infants. The data regarding mode of birth, presence of sepsis, APGAR score, jaundice, hypoglycemia, and weight loss was recorded in all infants. In group A, were more male patients than female patients (40 vs 10). In group B, the number of male and female patients was almost equal (26 vs 24). The difference in morbidities of both groups was significant (p<0.05). The incidence of neonatal morbidities was greater in the late preterm group except for hypoglycemia which was observed in more patients in normal-term infants (8% vs. 10%). The APGAR score in the preterm group was less than in the normal term group at 1 minute (7.28 vs. 7.92) (p=0.69) and at 5 minutes (8.38 vs. 8.65) (p=0.92). Neonatal morbidities like respiratory diseases, jaundice, hypoglycemia, sepsis, and weight loss of more than 10% are common in late preterm infants.